Designing a pepper harvester end effector - Tiong, I.H (Universiti Malaysia Sarawak, UNIMAS, 2010)
The cultivation of pepper (Piper Nigrum) is widely cultivated around the world including Malaysia. Malaysia is one of the major exporter of pepper in the world with Sarawak contributes 95% of the production. The harvesting process is normally done by local workers and there is no mobile robot solution. The development of mobile robot to harvest the pepper is still in research level. The purpose of this project is to design a pepper harvester end effector which able to pluck the pepper berries more efficiently. An axiomatic design approach has been used to accurately identify the needs and requirements in designing the end effector. Through this approach, the designer will be able to point out the limitation, function requirement and the design parameter by decomposing each function to multiple sub layers. The end effector developed in this research is to be attached to the existing design of mobile robots body. The end effector is made up a series of aluminum links which joint by universal joint. The actuator system being applied to this design is cable servo motor. The conceptual this design is hypothesize to be able to adapt to the pepper plantation.